Elucidation of host cell response to the immunogen mycolic acid extract of Corynebacterium pseudotuberculosis in goats - Ahmed Odhah, Mohammed Naji (2018)
Corynebacterium pseudotuberculosis is the causative agent of caseous lymphadenitis (CLA), a chronic disease of sheep and goats, characterized by the formation of suppurative abscesses in superficial and visceral lymph nodes and in the internal organs of small ruminants. The occurrence of CLA has been documented in the United States, Canada, Australia, New Zealand, South Africa, Brazil and Malaysia with the small ruminants being predominant. The prevalence of CLA among small ruminants in Malaysia is currently estimated at 30% and thus is a noteworthy disease in Malaysia. However, the paucity of information in the literature relating to the extraction of mycolic acids (MAs) from C. pseudotuberculosis and its host cell response and the need to investigate the mechanism by which C. pseudotuberculosis and its immunogen MAs adversely affects goats is an attempt to undertake this study. This study was also designed to test the hypothesis that acute phase protein, antibodies, mainly IgM and IgG, estrogen and progesterone hormones, cytokine, especially, IL-1β and IL-6 can be used as a diagnostic aid for CLA. Twelve clinically healthy crossbred female Boer goats aged between 16-20 months, weighing 25-35 kg were used in this study. The experimental animals were nonpregnant, non-lactating and had no history of vaccination against CLA. The goats were divided into three groups (A, B and C) consisting of 4 animals each. The control group A was administered with 2 ml of sterile phosphate buffered saline (PBS) intradermally, whereas group B was inoculated with 2 ml of mycolic acid (1 gm/ml) intradermally and group C was inoculation with 2 ml of 1×109 CFU of C. pseudotuberculosis intradermally. Animals were monitored for the entire period (3 months) of the experiment for signs of the disease and blood samples were collected intermittently. The blood sample was collected in heparinized, EDTA plain tubes for haematological, acute phase protein (APP), IgM and IgG antibodies, sex hormones (estrogen and progesterone) and cytokine (IL-1β and IL-6) analysis. At the end of the study, post-mortem examination of gross lesions was conducted mainly on lung, heart, liver, kidneys, spleen, ovaries, fallopian tubes, uterus, cervix, vagina as well as external and internal lymph nodes were examined to morphologic diagnosis tissues samples also collected for histopathology for analysis of cellular changes. The inoculated goats in both C. pseudotuberculosis and MAs groups showed significant increase (p<0.05) in body temperature, heart rate, respiratory rate and sharp decrease in rumen motility was observed. Moreover, body condition score was significantly decreased (p<0.05) and enlargement with rupture of injection sites in both treated groups. Superficial lymph nodes showed abscess formation in C. pseudotuberculosis inoculated group only. Varying levels of effect on hematological profile in both treatment compared to the control groups was revealed. The C. pseudotuberculosis inoculated goats showed significant decrease (p<0.05) in red blood cell count and significant increase (p<0.05) in packed cell volume. On the other hand, significant decreases (p<0.05) in the haemoglobin and mean corpuscular hemoglobin concentration in both C. pseudotuberculosis and MAs groups. There was also a notable increase in the levels of white blood cells, neutrophils and lymphocytes in both C. pseudotuberculosis and MAs groups. Meanwhile, haptoglobin was increased from weeks 1-3 and reduced to within the normal range at week 4 in C. pseudotuberculosis group while the MAs group showed significant increase (p<0.05) in the these only in weeks 1 and 2. Similar treats were observed in serum amyloid A except that the increase observed in the C. pseudotuberculosis group was only in weeks 1 to 4. In addition, a significant increase (p<0.05) in IgM in C. pseudotuberculosis group was observed from weeks 2 to 5, while MAs group showed significant increase (p<0.05) from weeks 1 to 3. The level of the IgG was response in C. pseudotuberculosis group was significantly (p<0.05) higher throughout the study period for both groups. The concentration of IgG was steadily increased in the C. pseudotuberculosis and MAs treated groups peaking at week 9 with 32.82±8.56 ng/ml in C. pseudotuberculosis group and 28.41±1.27 ng/ml in MAs group. In addition estrogen hormone showed significant increase (p<0.05) in both treated groups from week 1 to 5 in C. pseudotuberculosis group and weeks 1 to 3 in MAs group. On the other hand progesterone hormone showed significant increase (p<0.05) from weeks 1 to 6 and 1 to 3 in C. pseudotuberculosis and MAs groups respectively. Furthermore, the cytokine (IL-1β) and was increased significantly (p<0.05) in weeks 2, 3, 5, 6, 9 and 10 for the C. pseudotuberculosis group, and week 5 to 10 in MAs group. In a similar vein, IL-6 showed significant increased (p<0.05) in week 5, 6, 7 and 8 for the C. pseudotuberculosis group, while MAs group showed significant increased (p<0.05) in week 2, 3, 4, 5, 6 and 8 compared to the untreated control group. Post mortem examination of vital and reproductive organs and also internal and external lymph nodes showed mild to severe pathology in the C. pseudotuberculosis group, while the MAs group showed mild to moderate lesions. On the other hand, high rate of gross pathological changes were recorded in both groups in the vital organs and lymph nodes. There were, no significant gross pathological changes were observed in the reproductive organs in both groups. In vital organs such as lung, heart, liver, kidneys, spleen, the main gross pathological lesions observed were congestion, haemorrhage, fatty atrophy and abscessation in C. pseudotuberculosis group. Moreover, the lymph nodes, revealed high percentage of abscess formation in different sizes in all goats in group C. While MAs group did not show any abscess in the visceral organs or the lymph nodes and reproductive organs despite enlargement of the lymph nodes. The histopathological changes observed were significant in C. pseudotuberculosis inoculated group and the pathologies include congestion, oedema, and infiltration of inflammatory cells, degeneration and necrosis in the vital, reproductive organs and lymph nodes. The MAs inoculated group showed significant congestion, oedema, degeneration and necrosis. Detection of the bacteria using conventional PCR revealed 100% detection of the bacteria in the C. pseudotuberculosis inoculated group. Conclusively, this study was able to demonstrate varying clinical manifestations from both C. pseudotuberculosis and MAs inoculated groups. Classical signs of CLA were observed in the C. pseudotuberculosis group specifically abscess formation in superficial lymph nodes, while MAs group showed no abscessation. On the other hand, C. pseudotuberculosis and MAs showed significant changes in all heamatological parameters, acute phase protein, IgM and IgG antibodies, estrogen and progesterone concentrations. Significant changes were also observed in the cytokines (IL-1β and IL-6) Different response pattern in the group compared to C. pseudotuberculosis for the haematological parameters, acute phase protein, IgM and IgG antibodies, reproductive hormones as well as cytokines indicate different mechanisms. The gross and cellular changes were typical of CLA lesions in C. pseudotuberculosis inoculated group whilst MAs inoculated group showed less gross changes however, the cellular changes were severe, indicating the effect of MAs on tissues.